ORGAN DALAM AYAM ISA BROWN UMUR 104 MINGGU YANG DIBERIKAN KALSIUM DARI CANGKANG KERANG DALAM RANSUM - IKU M. S. F.; G. A. M. K. DEWI; M. WIRAPARTHA (Fakultas Peternakan Universitas Udayana, 2021)
The aim of the study was to determine the effect of calcium from seashells flour in commercial rations on the internal organs of isa brown chickens aged 104 weeks, carried out in Pesedahan Village, Manggis District, Manggis Regency, Karangasem for 4 weeks. Using a completely randomized design (CRD) with four treatments consistend of five replications used three isa brown chikens. The treatments given were commercial rations whithout adding seashells flour (P0/control), commercial ransum plus 1%, 2% and 3% calcium seashells flour (P1, P2, and P3). The variables observed were hearth weight, liver weight, pancreatic weight, bile weigthand spleen weight. The results showed that the addition of calcium shellfish flour 1%, 2%, and 3% in commercial rations had no significant effect on hearth weight, liver weight, pancreatic weight, bile weigthand spleen weight. Based on the results of the study it can be concluded that the addition of calcium seashells flour 1%, 2%, and 3% in commercial rations did not affect heart weight, liver weight, pancreatic weight, bile weigth and spleen weight